A Comparative Study of Potential Energy Curves Analytical Representations for CO, N2, P2, and ScF in Their Ground Electronic States - Rasheed, Nmareq Khalid; Ayaash, Adil Nameh (Iraqi Journal of Science, 2021)
In this study, a detailed comparative analysis of four different potential energy functions is elaborated. These potential energy functions namely are Morse, Deng-Fan, Varshni, and Lennard-Jones. Furthermore, a mathematical representation for long-range region is elucidated. As a study case, four diatomic molecules (CO, N2, P2, and ScF) in their electronic ground states were chosen. Subsequently, the corresponding dissociation energy as well as some spectroscopic parameters were calculated accordingly.